'I feel the weather and you just know'. Narrating the dynamics of commuter mobility choices. (July 2022) - Barr, Stewart; Lampkin, Sal; Dawkins, Laura; Williamson, Daniel
Abstract: Efforts to promote travel behaviour change have frequently deployed social marketing strategies that are based on characterising populations into discrete target groups through quantitative segmentation techniques. Such techniques provide an important basis for understanding behavioural choices and motivations, frequently using psychological constructs that can be used for planning interventions. However, there are limitations to what a solely quantitative approach can offer practitioners in terms of understanding the dynamics of travel behaviour and the meanings associated with personal mobility that can be used to design appropriate interventions. In this paper we provide evidence to argue for a mixed-methods approach, where insights from quantitative segmentation and qualitative data can be used to reveal the experiential nature of factors that influence travel decision making. To pursue this argument we present findings from research with commuters in the city of Exeter, South West England. Using data from five workshops, we illustrate the ways in which participants articulated and gave meaning to a series of travel mode influences identified using quantitative segmentation techniques for specific commuter groups (private car, public transport, walking, cycling and a combination of modes). We demonstrate how both understanding the dynamism of travel behaviour and revealing its meanings can present opportunities for designing interventions, offering pathways to promote shifts away from carbon intensive transport.